NEOLIBERALISM IN EFL TEXTBOOK : CONTENT ANALYSIS - Anggraeni, Galuh Ajeng; Santosa, Imam (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
There are a lot of Ideologies that influenced the educational world, and one of them is Neoliberalismm. The incorporation of neoliberalism values in an English textbook could be a common thing and the usage of local culture in English textbooks is often vanquished by the target culture content. This study provided how the values of neoliberalism appear on textbooks with local and international based curricula. This research used content analysis method. EFL Textbook K13 revision curriculum base and Cambridge curriculum base for grade 11 will be use as samples in this research. The instrument was used in this study is table analysis. In the end of the study, results showed neoliberalism value delivered within EFL textbook steadily with text in the textbook both in international EFL textbook and local EFL textbook.